River Plume Rooted on the Sea-Floor: Seasonal and Spring-Neap Variability of the Pearl River Plume Front - Zhi, Haihang; Wu, Hui; Wu, Jiaxue; Zhang, Wenxia; Wang, Yihe (Frontiers in Marine Science, 2022)
The buoyant river plume front exhibits substantial variability in the sea surface under energetic external forcing. Although highly dynamic, the river plume is often “rooted” at specific locations through the bottom river plume front. In this study, we addressed this mechanism using the Pearl River plume as an example based on a well-validated numerical model. With this model, we described the spatiotemporal characteristics of the Pearl River salinity front. It was found that, although the surface Pearl River plume features bimodal extension in summer and winter seasons, owing to the reversal of the seasonal monsoon wind, there is a relatively stable bottom front extending from the river mouth to the downstream region (i.e., in the direction of propagation of Kelvin Wave). The occurrence probability of the bottom front showed that the front location varies only slightly and fixes at ∼8-m isobath. The Empirical Orthogonal Function (EOF) analysis demonstrated that runoff, wind, and tide are major regulating factors. These three factors jointly control the strength and position of the bottom front. In particular, the bottom front moves offshore during the spring tide but onshore during the neap tide, respectively, indicating a different mechanism from the classic frontal trapping theory. The sensitivity experiment without tide indicated that the bottom plume front shrinks significantly, and the river plume becomes more dynamic since it is no longer rooted on the seafloor.